The Subbromide Bi5Br4 – On the Existence of a Hidden Phase - Pabst, Falk; Chang, Jen-Hui; Finzel, Kati; Kohout, Miroslav; Schmidt, Peer; Ruck, Michael (Zeitschrift für Anorganische und Allgemeine Chemie, 2019)
Black and irregularly shaped crystals of the bismuth-rich bromide Bi5Br4 were obtained as a by-product of the reaction of CsBr, Bi, and BiBr3. X-ray diffraction on a single-crystal revealed its orthorhombic structure with the space group Pmmn (no. 59) and lattice parameters a = 1800.0(2) pm, b = 1476.1(1) pm, and c = 924.5(2) pm at 296 K. The structure is composed of Bi8 2+ and Bi9 5+ polycations and bromidobismuthate(III) anions according to the structured formula Bi5Br4 = Bi20Br16 = Bi8 2+Bi9 5+[BiBr5]2–[Bi2Br11]5–. Bi5Br4 is the bismuth-richest among the bismuth subhalides containing isolated polycations. Extensive differential scanning calorimetry studies indicate that Bi5Br4 decomposes at 262 °C, i.e. one degree below the bismuth-rich eutectic at 263 °C. All attempts towards a rational synthesis yielded predominantly the neighboring phases BiBr and Bi6Br7.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Bismuth; Bromine; Cluster compounds; Phase diagrams; Polycations